Molecular features underlying the higher ecological success of C. trachomatis E and F genotypes - Nunes, A. (2012)
In the light of the >98% genomic similarity among Chlamydia trachomatis serovars, the higher worldwide ecological success of E and F is enigmatic. We intend to provide a quick overview of the molecular data that distinguish these from the remaining strains. Examples are: - E and F possess a similar chromosomal genetic make-up distinct from the remaining genotypes. Some loci linked to this independent co-segregation comprehend membrane proteins, hypothetical virulence factors, and regulatory regions (published data). - Some loci reveal nonrandom mutational patterns, where mutations exclusive of E and F are clustered in specific protein domains, likely promoting strains functional and/or structural attributes (published data). - Based on data from a worldwide survey, MOMP of E and F exhibit the lowest mutation rate (22.3-fold lower), implying more fitted antigenic profiles to deal with host immunity (published data). - The likelihood of E and F strains to undergo genetic recombination is about 12-fold lower than that of the other genotypes (P<10-2), suggesting a putative clonal evolution, where superimposed favorable clones may be strongly maintained in vivo (preliminary data from our lab). - Strains E and F do not seem to originate higher infectious load in vivo, when compared with other genital genotypes (published data). Full-genomic data from multiple and diverse clinical isolates will be essential to decipher the secret behind the higher ecological success of E and F strains.